Hotel management graduates perception of work conditions and the moderating effect of salary on work motivation in the hotel industry during the Covid-19 pandemic - Ferdian, Feri; Abrian, Youmil; Suyuthie, Hijriyantomi; Chair, Ira Meirina (Universitas Negeri Padang, 2021)
This study aimed to analyze the hotel management graduates' perception of work conditions and the moderating effect of salary on work motivation in the hotel industry during the COVID- 19 pandemic. This research was conducted with a quantitative approach. The total population was 670 hotel management graduates with the sample's determination based on the type of purposive sampling. The sample size of the study is 20% of the total population (134 graduates) who are estimated to work in the hotel industry. A total of 134 respondents were successfully collected. The data analysis technique used is Partial Least Square Structural Equation Modelling (PLS-SEM). The results showed that: There is a significant effect of work condition toward hotel management graduates’ work motivation in the hotel industry during the COVID- 19 pandemic and there is a significant moderating effect of salary toward the relationship between work condition and hotel management graduates’ work motivation in the hotel industry during the COVID- 19 pandemic. What could be said from the result of the study is that the impact of work conditions toward work motivation in the hotel industry during the COVID-19 pandemic would be increased with the presence of salary.